Identification of inhibitors regulating cell proliferation and FUS-DDIT3 expression in myxoid liposarcoma using combined DNA, mRNA, and protein analyses - Svec, David; Dolatabadi, Soheila; Thomsen, Christer; Cordes, Nicole; Shannon, Mark; Fitzpatrick, Paul; Landberg, Göran; Åman, Pierre; Ståhlberg, Anders (Laboratory investigation; a journal of technical methods and pathology, 2018)
FUS-DDIT3 belongs to the FET (FUS, EWSR1, and TAF15) family of fusion oncogenes, which collectively are considered to be key players in tumor development. Even though over 90% of all myxoid liposarcomas (MLS) have a FUS-DDIT3 gene fusion, there is limited understanding of the signaling pathways that regulate its expression. In order to study cell proliferation and FUS-DDIT3 regulation at mRNA and protein levels, we first developed a direct cell lysis approach that allows DNA, mRNA, and protein to be analyzed in the same sample using quantitative PCR, reverse transcription quantitative qPCR and proximity ligation assay, respectively. We screened 70 well-characterized kinase inhibitors and determined their effects on cell proliferation and expression of FUS-DDIT3 and FUS at both mRNA and protein levels in the MLS 402-91 cell line, where twelve selected inhibitors were evaluated further in two additional MLS cell lines. Both FUS-DDIT3 and FUS mRNA expression correlated with cell proliferation and both transcripts were co-regulated in most conditions, indicating that the common 5' FUS promotor is important in transcriptional regulation. In contrast, FUS-DDIT3 and FUS protein levels displayed more cell line dependent expression. Furthermore, most JAK inhibitors caused FUS-DDIT3 downregulation at both mRNA and protein levels. In conclusion, defining factors that regulate FUS-DDIT3 expression opens new means to understand MLS development at the molecular level.
Keywords: Gene Expression Regulation, Neoplastic; DNA; regulace genové exprese u nádorů; proliferace buněk; RNA, Messenger; myxoidní liposarkom; Humans; Oncogene Proteins, Fusion; nádorové buněčné linie; lidé; protinádorové látky; fúzní onkogenní proteiny; messenger RNA; Cell Line, Tumor; Cell Proliferation; Liposarcoma, Myxoid; Antineoplastic Agents